Policy-driven collaborative arrangements and competency development – a case of Malaysia's MSC flagship networks. (17th December 2009) - Omar, Aliza Akmar; Mohan, Avvari V.
This paper presents the results of a survey done among organisations participating in flagship networks in Malaysia's Multimedia Super Corridor (MSC Malaysia) project. The MSC flagships are an integral part of MSC Malaysia and are inter-organisational networks, built through policy-driven collaborative arrangements, to help participating organisations develop innovative applications and achieve sustainable competitive advantage. These directed networks of exchange relationships are intended to create value in that the creativity and talent derived out of such an environment is perceived to result in certain competencies. Preliminary findings indicate that the three network groups are identified as having different forms or structures. The results of the statistical analysis indicate the following – that network structure is important in facilitating results for the organisations committed to the networks, where different network forms display different combinations of network characteristics and correspondingly, the different combinations lead to differing strengths in different competencies. It is especially significant where the focus is on policy-driven inter-organisational networks in developing economies.